(untitled) (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2026)
Arboreal locomotion represents one of the most demanding biomechanical challenges in vertebrate evolution, requiring precise coordination of grasping appendages, postural stability, balance, and rapid three-dimensional navigation through structurally complex canopy environments. The evolutionary response to these demands has produced remarkable convergent morphological solutions across phylogenetically disparate mammalian lineages, including primates, marsupials, rodents, xenarthrans, and carnivorans. This study conducted a comprehensive comparative morphological analysis of 214 arboreal mammal species spanning 11 orders, quantifying 38 skeletal, muscular, and external morphological traits associated with arboreal locomotor performance. Phylogenetic comparative methods – including phylogenetic generalised least squares (PGLS), ancestral state reconstruction, and evolutionary rate analysis – were applied to a time-calibrated molecular supertree to distinguish convergent evolution from phylogenetic inertia. Grip strength relative to body mass, hindlimb-forelimb length ratio, tail prehensility index, and claw curvature were identified as the four traits most strongly associated with locomotor mode across the dataset (PGLS R2 = 0.74-0.87, all p < 0.001). Convergent evolution of prehensile tails occurred independently at least seven times across Neotropical and Afrotropical lineages, with evolutionary rate analyses revealing significantly accelerated morphological divergence following transitions to fine-branch arboreal niches (sigma2 increase: +3.4-fold, p < 0.001). Body mass strongly constrained trait diversification, with species above 10 kg showing convergent adaptations toward below-branch suspension and reduced digital dexterity. These findings illuminate the mechanistic links between ecological demands, biomechanical constraints, and macroevolutionary patterns in one of the most diverse adaptive radiations in mammalian history.